Culture as an indigenous tourism product of Mah Meri community in Malaysia - Kunasekaran, Puvaneswaran; Gill, Sarjit S.; Talib, Ahmad Tarmizi; Redzuan, Ma'rof (Marsland Press, 2013)
This paper presents the significant role of culture which is utilized by the Mah Meri community in Pulau Carey, Malaysia to practice sustainable tourism. Preliminary study was conducted at Kampung Sungai Bumbon which is a well established indigenous tourism destination in Malaysia. In-depth interview which was used as the qualitative data collection method helped the researchers to holistically understand the community resources which can encourage sustainable tourism practice. Cultural tourism products like wood carvings, weavings, Main Jo’oh dance and Ari Moyang are the main attributes which contribute to tourism development. This study reveals that the community is proud of its culture. However, the community feels that their culture and tourism gradually facing great threat because of the scarcity of natural resources. It is hoped that the findings of this study will contribute to existing literature in the indigenous tourism ground that could be an addition to the social exchange theory current standing.